2016
DOI: 10.1111/jpn.12568
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition affects growth rate, organ size and skeletal muscle satellite cell activity in newborn calves

Abstract: Plane of nutrition effects on body, tissue and cellular growth in the neonatal calf are poorly understood. The hypothesis that a low plane of nutrition (LPN) would limit skeletal muscle size by reducing fibre growth and muscle progenitor cell activity was tested. At birth, calves were randomly assigned to either a LPN (20% CP, 20% fat; GE=1.9 Mcal/days) or a high plane of nutrition (HPN; 27% CP, 10% fat, GE = 3.8 Mcal/days) in a 2 × 3 factorial design to test the impact of diet on neonatal calf growth, organ w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The differences in plasma leptin and adiponectin at the end of the study most likely do not result from different endogenous production due to variable body fat in COL and FOR calves. The body fat content in neonatal calves is low; for instance, percentage of perirenal fat in 2-wk-old calves is about 0.1 to 0.2% of carcass weight but is about 1.1 to 1.7% of carcass weight in dairy cows (Drackley et al, 2014;MacGhee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in plasma leptin and adiponectin at the end of the study most likely do not result from different endogenous production due to variable body fat in COL and FOR calves. The body fat content in neonatal calves is low; for instance, percentage of perirenal fat in 2-wk-old calves is about 0.1 to 0.2% of carcass weight but is about 1.1 to 1.7% of carcass weight in dairy cows (Drackley et al, 2014;MacGhee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When calves are provided with a high plane of nutrition, the cross-sectional area of their muscle fibers was significantly increased after 8 wk when compared with those animals receiving a low plane of nutrition (MacGhee et al, 2017). Additionally, providing a high plane of nutrition results in SC with a significantly increased mitotic index after 2 wk, but a significantly decreased mitotic index after 4 wk when compared with calves receiving a low plane of nutrition (MacGhee et al, 2017). This research demonstrates the first report in cattle of how nutrition specifically impacts proliferation and differentiation of SC in postnatal life.…”
Section: Impact Of Nutrition On Satellite Cells Postnatallymentioning
confidence: 96%
“…Another study in poultry showed that altering the methionine:cysteine ratio in the diet affected SC and subsequent muscle growth in the pectoralis major (Powell et al, 2013). A recent study showed that providing either a low or high plane of nutrition (1.9 vs. 3.8 Mcal of gross energy/d) to dairy bull calves altered SC activity and skeletal muscle growth (MacGhee et al, 2017). When calves are provided with a high plane of nutrition, the cross-sectional area of their muscle fibers was significantly increased after 8 wk when compared with those animals receiving a low plane of nutrition (MacGhee et al, 2017).…”
Section: Impact Of Nutrition On Satellite Cells Postnatallymentioning
confidence: 99%
See 1 more Smart Citation
“…At 210 days of age, after a period of feed restriction of H-L treatment, the average tail length, tail width, and tail circumference of lambs in the H-L group were lower than H-H lambs (P < 0.05; Table 4) but showed no difference compared with that of the L-H group (P > 0.05; Table 4). Animal growth has been defined as the net accretion of protein and fat in respective tissues, controlled by nutrition, environment, and genetic capacity to grow [31]. Hamouda and Atti [32] revealed that in young lambs, carcass adiposity and particularly fat tail reduce Barbarine meat value as the lamb grows.…”
Section: Tail Measuresmentioning
confidence: 99%